2019
DOI: 10.3390/cancers11081118
|View full text |Cite
|
Sign up to set email alerts
|

The Biological and Clinical Relevance of Inhibitor of Growth (ING) Genes in Non-Small Cell Lung Cancer

Abstract: Carcinogenic mutations allow cells to escape governing mechanisms that commonly inhibit uncontrolled cell proliferation and maintain tightly regulated homeostasis between cell death and survival. Members of the inhibition of growth (ING) family act as tumor suppressors, governing cell cycle, apoptosis and cellular senescence. The molecular mechanism of action of ING genes, as well as their anchor points in pathways commonly linked to malignant transformation of cells, have been studied with respect to a variet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…These act as tumor suppressors, regulating cell cycle, apoptosis, and cellular senescence. The authors proposed them as clinically useful biomarkers in the detection and prognosis of lung cancer ( 523 ).…”
Section: The Escape Of Cancer Stem Cells From Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…These act as tumor suppressors, regulating cell cycle, apoptosis, and cellular senescence. The authors proposed them as clinically useful biomarkers in the detection and prognosis of lung cancer ( 523 ).…”
Section: The Escape Of Cancer Stem Cells From Therapymentioning
confidence: 99%
“…Inhibition of the cyclin-dependent kinase 4/6 (CDK)-RB pathway by a novel drug, SHR6390, resulted in reducing the levels of Ser780-phosphorylated RB protein and correlated with the G1 arrest as well as with cellular senescence in a wide range of human RB + tumor cells in vitro (520). Xiang et al identified seven senescence-associated genes (SAGs, Table 8) significantly decreased in senescent cells and increased in HCC (523).…”
Section: Therapy-induced Senescence: Its Hallmarks Biomarkers and Its Role In Csc Generationmentioning
confidence: 99%
“…In GO analysis, biological processes were mostly enriched in sister chromatid segregation, regulation of cell aging, spindle organization, and mitotic nuclear division. Dysregulated cell–cycle machinery, uncontrolled proliferation, and resistance to programmed cell death feature cancers, including NSCLC ( Sherr, 1996 ; Hanahan and Weinberg, 2000 ; Smolle et al, 2019 ). Due to the paucity of well-proven therapies or vaccines, inhibiting cell division may be a good way to control COVID-19, which shares a similar goal with NSCLC treatment ( Borcherding et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that ING proteins are involved in a wide variety of cellular processes including DNA repair, histone methylation and acetylation, senescence, cell growth, colony formation, apoptosis, cell cycle control, chromatin remodeling, and angiogenesis [9,13,14]. Mutations and altered expressions of INGs have been reported in different types of cancers including lung cancer, osteosarcoma, oral squamous cell carcinoma, breast cancer, prostate cancer, gastric cancer, colorectal cancer, and laryngeal squamous cell carcinoma [15][16][17].…”
Section: Early Onlinementioning
confidence: 99%